2022
DOI: 10.1108/k-04-2022-0552
|View full text |Cite
|
Sign up to set email alerts
|

Women in travel and tourism: does fear of COVID-19 affect Women's turnover intentions?

Abstract: PurposeThe purpose of this study was to examine the role of fear of COVID-19 and job stress on women's turnover intentions in the hospitality industry (travel agencies). Also, the mediating role of work-family conflict was examined.Design/methodology/approachThree theoretical approaches of importance for framing issues of fear of COVID-19, job stress, work-family conflict and women's turnover intentions. Using the purposive sampling technique, the participants for the current paper were selected from the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 111 publications
1
5
0
Order By: Relevance
“…Some psychological effects of the COVID-9 pandemic are depression, anxiety, stress, and fear ( Nabi et al, 2022 ; Obuobisa-Darko, 2022 ). The findings from this study are consistent with several studies carried out in developed countries, which have confirmed a positive relationship between COVID-19 and turnover ( Chen & Qi, 2022 ; Li et al, 2022 ; Uludag et al, 2022 ). These findings can be explained from the perspective that employees' lives, safety, and well-being have been threatened; there was an increase in the mortality rate of employees during the COVID-19 period which made working in the workplace a threat to their lives, thus the relationship with turnover.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Some psychological effects of the COVID-9 pandemic are depression, anxiety, stress, and fear ( Nabi et al, 2022 ; Obuobisa-Darko, 2022 ). The findings from this study are consistent with several studies carried out in developed countries, which have confirmed a positive relationship between COVID-19 and turnover ( Chen & Qi, 2022 ; Li et al, 2022 ; Uludag et al, 2022 ). These findings can be explained from the perspective that employees' lives, safety, and well-being have been threatened; there was an increase in the mortality rate of employees during the COVID-19 period which made working in the workplace a threat to their lives, thus the relationship with turnover.…”
Section: Discussionsupporting
confidence: 93%
“…These findings can be explained from the perspective that employees' lives, safety, and well-being have been threatened; there was an increase in the mortality rate of employees during the COVID-19 period which made working in the workplace a threat to their lives, thus the relationship with turnover. Since employees’ fear and anxiety about COVID-19 have been shown to increase their turnover intentions ( Chen & Qi, 2022 ; Kokubun et al, 2022 ; Uludag et al, 2022 ) as well as turnover, it can thus be concluded that the anxiety, fear, and stress of employees about COVID-19, explains the relationship between COVID-19 and turnover intention.…”
Section: Discussionmentioning
confidence: 99%
“…Literature has offered abundant indications regarding the adverse impacts of COVID-19 on service employees' work behavior. The anxiety, hopelessness and negative feelings caused by COVID-19 resulted in frequent absenteeism, a propensity to be late for work (Karatepe et al , 2021), increased work-family-conflict (Uludag et al , 2022) and decreased work contribution and effort (Liu et al , 2021). According to Khawaja et al (2021), COVID-19 worry can instigate employees' depression, anxiety and stress.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…SLof as a mediator COVID-19 has a significant impact on hospitality employees' mental health. It also increases their work-family-conflict (Uludag et al, 2022), depression, anxiety (Khawaja et al, 2021;Tengilimo glu et al, 2021), absenteeism (Karatepe et al, 2021) and deviant behavior (Liu et al, 2021). Nevertheless, to accomplish and coordinate organizational activities, organizations rely on group and teamwork (Stouten and Liden, 2020).…”
Section: Slof and Odmentioning
confidence: 99%
See 1 more Smart Citation